In Silico Pharmacogenomic Analysis of Alcohol Dehydrogenase Involved in Alcoholism - SINGH SATENDRA; MECARTY S. D.; JAIN P.A.; GAUTAM B.; FARMER R.; YADAV P.K.; RAM G.D. (International Journal of Pharma and Bio Sciences, 2010)
Alcoholism is a disease characterized by lack of a person to metabolize the alcohol efficiently. Pharmacogenomic analysis deals with study how different individuals behave towards same drug or chemical. The present work examined Insilco sequence and structural differences in the isoenzymes of alcohol dehydrogenase involved in alcohol metabolism. Methods: Experiment, identified ADH1B, ADH1A, ADH1C and ADH4 as four different alcohol dehydrogenase isoenzymes, their sequences in the FASTA format was retrieved form uniprot knowledgedatabase. Sequence alignment, dendogram generation, motif identification, secondary structure prediction was carried out and examined with the help of different computational programs. Results: Multiple sequence alignment, Phylogenetic tree, amino acid composition, Percentage of different secondary structures reflect high degree of similarity in the results for ADH1B, ADH1A and ADH1C except there are some significant deviations in the results for ADH4. While analyzing the amino acids of active site region it was found that five out of nine amino acids are identical but four amino acid showed some variations. Ser at position 48 is replaced by Thr in ADH1B, ADH1A and ADH4. His at position 51, Ala at position 317 and Cys at position 146, is mutated with Thr in all three cases and all three mutations have occurred only in case of ADH4.Insilco analysis suggests that minimum mutations took place in the active site region of ADH1C, followed by ADH4, ADH1B and ADH1A. It can be concluded that individuals may inclined towards alcoholism either due to the absence of normal form of isoenzyme or presence of mutated form of isoenzyme (Pharmacogenomics), which is unable to perform its normal function of metabolism.